A Comparative Analysis of Human Trafficking: The United States of America (USA) and the Republic of South Africa (RSA) - Lanier, Mark M.; Farrell, C. Thomas; Bezuidenhout, Christiaan (International Journal of Criminology and Sociology, 2014)
Human trafficking is a serious global problem that transcends international borders and disciplinary boundaries. It presents a conglomeration of problems generally dealt with by public health, criminal justice, social service and immigration agencies. Victim advocates state that millions are victimized each year. The data suggest that law enforcement agencies perceive human trafficking to be of greater, or equal, concern for the myriad of social institutions and participants affected by human trafficking than for law enforcement, itself. Policy recommendations are to refocus the law enforcement response - which may include various approaches that can simultaneously benefit public health - by incorporating an Epidemiological Criminology framework to help to guide the development of more systematic and integrative insight into the world of human trafficking.